1989
DOI: 10.1038/bjc.1989.104
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative histological changes in murine tail skin following photodynamic therapy

Abstract: Summary Mice were treated by an intravenous injection of 2 mg of the photosensitising drug meso-tetra (sulphonatophenyl) porphine (TPPS) and 24 h later a 2.5cm length of their tails was exposed to visible light (photodynamic therapy, PDT). Using cross-sections from the centre of the treatment field, the absolute areas occupied by epidermis, dermis, hypodermis, tendon and bone, and also the total number and area of the blood vessels in the dermis and hypodermis, were compared between control and PDT-treated ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…These results are in accordance with the literature, which has demonstrated PDT effectiveness in periodontal treatment for both animals 2 and humans 4 .…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with the literature, which has demonstrated PDT effectiveness in periodontal treatment for both animals 2 and humans 4 .…”
Section: Discussionsupporting
confidence: 93%
“…It was also evident in the present study that group D animals, which received PDT treatment, showed less bone loss compared with group ND animals, which received only SRP treatment, at 7‐ and 30‐day periods. The beneficial effects of PDT in the periodontal disease could be explained not only by the local anti‐microbial activity, described previously, but also by the increased angiogenesis that supplies more oxygenation to the area (Benstead & Moore 1989).…”
Section: Discussionmentioning
confidence: 79%
“…The number of vessels visualized by the two different antibodies are not directly comparable as the staining was not performed on consecutive cryostat sections. A significantly increased number of blood vessels has previously been reported in the tails of mice 5 days after PDT using the photosensitizing drug mesotetra (sulphonatophenyl) porphine (TPSS) intravenously followed by exposure to visible light (16). This reaction was considered as a recovery phenomenon.…”
Section: Discussionmentioning
confidence: 98%